Penampil nomor lagu kidung pujian via bluetooth - Febri, Leon; Liman, Johansah; Harsono, Budi (Teknik dan Ilmu Komputer, 2012)
The worship songâs number displayer is a device that useful to show numbers of worship song into seven segment display using bluetooth as medium communication. This device is using handphone as a transmitter to write an input number which will be shown, a microcontroller to process the input data, bluetooth module as a receiver, and seven segment display as a number displayer.Realization of the device is provided by making the circuit diagram on a PCB (Printed Circuit Board) and software which is using Java programming language on the handphone. The device experiment is provided by making a trial for each block and also entirely. The conclusion that can be made from the experiment is this device can work well at the maximum range 24 meters in the room with no obstacles, and 14 meters in the room with obstacles.Â Keywords: Â bluetooth, microcontroller, seven segment